Study of the impact of aeration on the lubricant behavior in a tapered roller bearing: Innovative numerical modelling and validation via particle image velocimetry. (January 2022) - Maccioni, Lorenzo; Chernoray, Valery G.; Mastrone, Marco N.; Bohnert, Christof; Concli, Franco
Abstract: The air-lubricant interaction causes aeration which influences lubrication mechanisms in rolling-element-bearings. The goal of this paper is to develop a Computational Fluid Dynamics (CFD) model capable to take into consideration aeration. A new solver was implemented in the open-source environment OpenFOAM®. A dip lubricated tapered-roller-bearing was simulated with the new and a standard solver. The numerical predictions were compared with experimental data acquired on a dedicated test rig exploiting Particle Image Velocimetry (PIV). The comparison of the standard predictions and the experimental data for high shaft rotational speeds (higher level of aeration) shows discrepant results. On the other hand, the solver that takes aeration into account leads to results which are comparable to the experimental ones in all rotational ranges investigated via PIV. Highlights: Implementation of a solver capable of considering aeration on OpenFOAM®. Modeling and simulation of a tapered roller bearing in oil bath lubrication. PIV measurements into a tapered roller bearing through a sapphire outer ring. Comparison of the results of the simulations with the experimental ones. Experimental results validate the developed model.